protection of competition and prohibition of monopolistic practices with its executive regulation = قانون رقم 3 لسنة 2005 باصدار قانون حماية المنافسة ومنع الممارسات الاحتكارية ولائحته التنفيذية - Egypt. (2025)
Prime minister’s decree no. 2957 of the year 2010 amending certain provisions of the executive regulations of the law om competition protection and prevention of monopolistic practices promulgated by decree no. 1316 of the year 2005 Index: law no. 3 of the year 2005 promulgating the law on protection of competition protection and prohibition of monopolistic practices – prime minister’s decree no. 1316 of the year 2005 issuing the executive regulations of the law on competition protection and prevention of monopolistic practices as promulgated by law no. 3 of the year 2005 – part 1: general provisions and definitions – part 2: agreements and contracts between competing persons – part 3: agreement or contracting between a person and any of her/his suppliers or customers – part 4: abuse of control on a concerned market – part 5: public utilities and basic products – part 6: competition protection and monopolistic practices prevention agency – part 7: submission of reports, procedures o fact-finding and search, gathering factual materials, and receiving notifications قرار رئيس مجلس الوزراء رقم 2957 لسنة 2010 بتعديل بعض أحكام اللائحة التنفيذية لقانون حماية المنافسة ومنع الممارسات الاحتكارية الصادر بالقرار رقم 1316 لسنة 2005 قانون رقم 3 لسنة 2005 باصدار قانون جماية المنافسة ومنع الممارسات الاحتكارية – قرار رئيس مجلس الوزراء رقم 1316 لسنة 2005 باصدار اللائحة التنفيذية لقانون جماية المنافسة ومنع الممارسات الاحتكارية الصادر بالقانون رقم 3 لسنة 2005 – الباب الأول أحكام عامة وتعاريف – الباب الثانى الاتفاقيات والتعاقدات بين اشخاص متنافسة – الباب الثالث الاتفاق او التعاقد بين شخص واى من مورديه او من عملائه – الباب الرابع اساءة استخدام السيطرة على سوق معينة – الباب الخامس المرافق العامة والمنتجات الاساسية -- الباب السادس جهازامنافسة ومنع الممارسات الاحتكارية – الباب السابع تقديم التبليغات واجراءات التقصى والبحث وجمع الاستدلالات وتلقى والاخطارات